2015
DOI: 10.18357/ijih.102201515113
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the intergenerational effects of colonization: Aboriginal women with neurological conditions—their reality and resilience

Abstract: The "Understanding from Within" (UFW) project was part of the National Health Population Study of Neurological Conditions (NHPSNC), a 4-year study aimed at better understanding the scope of neurological conditions in Canada, and funded by the Public Health Agency of Canada. The goal of the UFW project was to develop a better understanding of how Aboriginal people conceptualize neurological conditions and the impacts on their families and communities, and the resources and supports needed to provide culturally … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 8 publications
(6 reference statements)
0
15
0
Order By: Relevance
“…Collaboration/partnerships with members of Indigenous communities should be used to inform health program design and development for CS to occur in health initiatives (HCC, 2012; Hole et al., 2015; Métis Centre of the National Aboriginal Health Organization [MCNAHO], 2013). Within a culturally safe health initiative, relationships among health-care providers and participants should incorporate both trust and respect; this is often developed over time by culturally competent health-care providers (Di Lallo, 2014; HCC, 2012; MCNAHO, 2013) who have respectful attitudes and values, and respect for the patient’s lifestyle and choices (Bourassa, Blind, Dietrich, & Oleson, 2015). Authors have suggested that embracing and incorporating Indigenous knowledge, informed by community members themselves, allows for a productive balance of biomedical and Indigenous ideas informing health care (Brooks-Cleator & Giles, 2016; Di Lallo, 2014; Ziabakhsh, Pederson, Prodan-Bhalla, Middgah, & Jinkerson-Brass, 2016).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Collaboration/partnerships with members of Indigenous communities should be used to inform health program design and development for CS to occur in health initiatives (HCC, 2012; Hole et al., 2015; Métis Centre of the National Aboriginal Health Organization [MCNAHO], 2013). Within a culturally safe health initiative, relationships among health-care providers and participants should incorporate both trust and respect; this is often developed over time by culturally competent health-care providers (Di Lallo, 2014; HCC, 2012; MCNAHO, 2013) who have respectful attitudes and values, and respect for the patient’s lifestyle and choices (Bourassa, Blind, Dietrich, & Oleson, 2015). Authors have suggested that embracing and incorporating Indigenous knowledge, informed by community members themselves, allows for a productive balance of biomedical and Indigenous ideas informing health care (Brooks-Cleator & Giles, 2016; Di Lallo, 2014; Ziabakhsh, Pederson, Prodan-Bhalla, Middgah, & Jinkerson-Brass, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…The theme of power sharing includes examining the distribution of power and empowering the patient. Providers of culturally safe interventions need to recognize their power and privilege and how it is inherent to the health-care structure within a postcolonial society (Bourassa et al., 2015; Giles, Hognestad, & Brooks, 2015). The practice of allowing patients to share in decision-making was recognized as a possible method to better distribute power (Di Lallo, 2014; Monchalin, Lesperance, & Logie, 2016).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Anderson, Kubik, & Hampton, 2010), violence against women of Indigenous background and its consequences remain of great concern. The multiple forms of oppression and abuse are associated with serious physical and mental health problems for Indigenous women (Bourassa, Blind, Dietrich, & Oleson, 2015; Kubik, Bourassa, & Hampton, 2009), including addictions (Firestone, Tyndall, & Fischer, 2015). Some characterize the mental health problems as “complex trauma” (Söchting, Corrado, Cohen, Ley, & Brasfield, 2007), while others describe it as “intergenerational trauma” (Roy, Noormohamed, Henderson, & Thurston, 2015).…”
mentioning
confidence: 99%
“…Many ideological perspectives, ideologies, and worldviews that are colonial and/or Westernized in nature are still being forced upon First Nation, Métis, and Inuit persons and their belief systems and practices continue to be disrespected through racist polices, legal systems and structural institutions (Baskin, 2011). This perpetuates oppressive structures and policies, such as laws and regulations, which disproportionately harm Indigenous persons (Bourassa, Blind, Dietrich & Oleson, 2015). Such marginalizing laws have created a strong distrust and reluctance from Aboriginal groups towards non Aboriginal people, governments and institutions.…”
Section: Colonization and Its Impactsmentioning
confidence: 99%